Studying The Factors Associated With Relapse Of Pulmonary Tuberculosis in Baghdad - AL-Jubouri, Adnan M.; Alobaidy, Muhammed W.; AL-Sabah, Hamza A.; Ouda, Sulaiman D. (Journal of the Faculty of Medicine Baghdad, 2013)
Background:  Relapse is defined as recurrent tuberculosis at any time after completion of treatment and apparent cure Recurrence of tuberculosis may occur as a result of relapsed infection due to the same Mycobacterium tuberculosis strain, or due to exogenous reinfection with a new strain.Objective: To study the factors associated with relapse of pulmonary  tuberculosis. Methods:. Across sectional study had been done in the chest and respiratory diseases teaching specialized center in Baghdad during the period from the  1st  of January 2010 to the 30th of July 2011. A total of 58 patients with  relapsed pulmonary tuberculosis were included in this study. For each patient.the fallowing variables were collected age, gender, marital status, regularity of treatment, diabetes mellitus, smoking, alcohol intake and  prisonment have been studied.Results: Mean age for all relapsed cases was 47.4years.A 53patients(91.4%) of relapse cases were married. There was only 30 patients(51.7%)of relapse cases  regular on  treatment. It was 15 patients (25.9%) contribute to about one forth (25.9%) of relapsed cases was diabetic. There was 28 patients (48.3%)of relapsed cases was smokers. A17 patients (29.3)% of them was prisons.Finaly 13 patients(22.4%) of relapsed  cases had history of alcoholic intake.Conclusions: Recurrence of tuberculosis was more common in  male, married, diabetic, prisoners, and history of alcohol patients and patients presenting at least one of the risk factor can benefit from the implementation of a post-treatment surveillance system for early detection of recurrence.